Gendered Female Characters in Ahmed Yerima’s Tuti and Yemoja - Ojediran, Oludolapo; Babatunde, Omobola Oyedepo; Emmanuel-Olowonubi, Oluwakemi, (Journal of Ecohumanism, 2024)
Gender roles and their representation in literature have long been subjects of critical examination, particularly in the context of African societies where cultural norms deeply influence societal structures and individual identities. In African drama, the depiction of male and female characters often mirrors traditional gender expectations, which can reinforce existing stereotypes and perpetuate gender inequalities. This study aims to analyze the portrayal of female characters in Yerima's Tuti and Yemoja, focusing on the ways these characters reflect and resist traditional gender norms. By employing a modified psychoanalytical framework by Barbieri, the research seeks to uncover the underlying biases and cultural assumptions that shape these portrayals. Our findings reveal that in a bias society like Africa, women’s beauty and education are threat and also seen as been proud. This study also reveals that a woman’s kindness and motherly nature is used against him and term weakness as portrayed by Yerima, where Titubi’s complementary role is challenged as taking up the responsibilities of her husband while Yemoja’s kindhearted is portrayed as been seduction by Esu and her husband Ogun. The study not only contributes to the academic discourse on gender and literature but also advocates for more equitable and diverse representations of gender in African drama.